Pengaruh Penerapan Missouri Mathematics Project terhadap Kompetensi Pemecahan Masalah dan Disposisi Matematis Siswa SMK Kelas X - Afla, Nurul; Wulandari, Wulandari; Qausar, Haves (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2024)
Students' low problem-solving ability and weak mathematical disposition are often attributed to the use of inappropriate instructional models and the limited opportunities provided for students to practice solving mathematical problems. To address this issue, an instructional model is needed that actively engages students in mathematical problem-solving while simultaneously fostering their mathematical disposition. One such model is the Missouri Mathematics Project (MMP). This study aims to investigate the effect of the Missouri Mathematics Project instructional model on students’ problem-solving skills and mathematical disposition. The research employed a quasi-experimental design using a nonequivalent control group posttest-only design. The population consisted of all tenth-grade students at SMK Negeri 7 Lhokseumawe. The sample was selected through purposive sampling, with class X-TKR serving as the experimental group and class X-PGL as the control group. The research instruments included a test and a questionnaire. The posttest was administered to assess students’ mathematical problem-solving ability, while the questionnaire measured their mathematical disposition. Hypothesis testing was conducted using an independent samples t-test at a significance level of 0.05. The results showed that the significance value (2-tailed) was 0.000. Based on this finding, it can be concluded that the Missouri Mathematics Project instructional model has a significant effect on students' problem-solving skills and mathematical disposition.